A hospitalidade na economia compartilhada: um estudo do site Airbnb, Brasil - POLAZZO, Ana Paula Carli (2018)
In the present research was referred to Hospitality in alternative means of hosting, promoted by the shared economy, specifically on the Airbnb website. The manifestation of Hospitality was approached with a focus on the shared economy, highlighting the current moment, where several services could be offered by the internet site, while virtual communities were formed allowing the narrowing of relations between individuals. The alternative lodging were described, initially with information of the historical passages and evolved to the discussion of the shared economy, detailing the operation of the Airbnb website. The host-guest relationship were considered within the context, going through the competitive advantage of this model. The problem of this research were approached with the question of: What is the perception of hospitality and quality by Brazilian users who have stayed through the Airbnb site in the last twelve months, with the general objective of: Identify in groups of Brazilian users of the services through the Airbnb website, what is the perception during the hosting. The specific objectives were: to evaluate the hospitality perceptions of the Brazilian users during the lodging; to evaluate the pleasure of Brazilian users during their stay; to evaluate the influence of the economic benefits perceived by the purchase of lodging and to evaluate the degree of satisfaction of the Brazilian users during the lodging. The hypotheses formulated to validate this study were: H1- Hospitality perceived by the user of the alternative means of accommodation positively influences the Satisfaction; H2- Perceived Pleasure by the user of alternative hosting media positively influences the satisfaction of alternative lodging services and H3- Perceived Economic Benefit positively influences the satisfaction of users of alternative lodging services. In the first stage of this study, the theoretical framework was elaborated through bibliographic research based on books and scientific articles published in periodicals. In the second stage, for the design of the research, quantitative approaches were made, with the application of a questionnaire based on a Likert type scale with people who stayed through the Airbnb site. The scales had the contribution of previous studies, notably: Hamari, Sjöklint and Ukkonen (2015). The data were tabulated later in the SmartPLS software for the assembly of the structural equations model, verification of the hypothesis and completion of the objective. The sample of the research pointed out that the feeling of security, reception and economic benefit are important factors in the perception of hospitality by the guests who use the virtual platform of the Airbnb website.